A Retrospective Assessment of Neuropathic Pain in Response to Intraneural Facilitation® Therapy and Neurovascular Index-Guided Food Elimination - Mark Bussell; Kyan Sahba; Hailey Jahromi; Mitra Rashidian; Jamie Hankins (Biomedicines)
Background/Objectives: To evaluate the effectiveness of our dual approach in treating neural ischemia. Methods: Researchers were able to retrospectively audit patient data collected from January 2022–September 2024. Patients were included if they received intraneural facilitation® (INF®), participated in neurovascular index (NVI)-guided food elimination, and completed pre and post pain-quality assessment scale (PQAS) forms in its entirety. Results: Eighteen of the twenty PQAS descriptive pain variables were significantly different pre- vs. post treatment: intense (p = 0.000), sharp (p = 0.002), hot (p = 0.020), dull (p = 0.022), cold (p = 0.005), sensitive (p = 0.000), shooting (p = 0.000), numb (p = 0.000), electrical (p = 0.000), tingling (p = 0.000), cramping (p = 0.000), radiating (p = 0.000), throbbing (p = 0.000), aching (p = 0.000), heavy (p = 0.000), unpleasant (p = 0.000), deep pain (p = 0.000), and intense surface pain (p = 0.000). Itchy (p = 0.058) and tender (p = 0.062) were not found to be significant. There was also significance in pain decrease in the three mean domains: paroxysmal (p = 0.000), superficial (p = 0.000), and deep (p = 0.000). Conclusions: This study suggests that blending a mechanical intervention (INF®) with a lifestyle modification (NVI-guided food elimination) is effective in improving PQAS scores in patients with peripheral neuropathy, indicating a possible reversal of neural ischemia and maintenance of capillary patency.